Feature Papers in Agriculture Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In the ever-changing world of agriculture, marked by the constant need to produce more food while balancing resource and sustainability demands, the creation of better farming equipment plays a crucial role. Embracing technology and innovation is key to tackling these challenges, and computer simulation stands out as a powerful tool in this endeavour. This Special Issue, titled "Using Computer Simulation for Agricultural Machinery Design and Development", explores the broad landscape of applying computer simulation techniques in agriculture. The publications covered various topics, including advanced modelling and simulation (DEM, FEM, CFD, SPH), performance optimisation, structural analysis, energy efficiency, human–machine interaction, and validation and verification. This Special Issue is more than a mere collection of papers; it is a driving force advancing the boundaries of agricultural machinery design and development through computer simulation.